Apllication of the Picture and Picture on Advertisement Text, Slogans, and Posters to Improve Learning Outcomes of Eighth Grade Students - Dyah Wiyati Kusumaningtyas; Aida Azizah; Wardani, Oktarina Puspita (Perspektif Pendidikan dan Keguruan, 2025)
The problem addressed in this study is the low level of students' understanding of advertisement texts, slogans, and posters, which is due to the lack of comprehensive explanations in the textbooks. The purpose of this study is to describe the implementation of the Picture and Picture learning method for this material as an effort to improve students' comprehension. This study uses a mixed-method approach, combining both quantitative and qualitative methods. Quantitative data were obtained through student test results, while qualitative data were collected through observation and documentation. The results show that the Picture and Picture method significantly improves student learning outcomes. Of the 16 students who participated as research samples, 12 students met the Minimum Completion Criteria (KKTP), with an average class score of 78.25. In addition, this method positively influenced students' motivation and engagement during the learning process. In conclusion, the Picture and Picture method can be used as an effective, engaging, interactive, and contextual alternative to enhance students’ understanding of advertisement texts, slogans, and posters.